Cell-Free DNA Sequencing Reveals Gene Variants in DNA Damage Repair Genes Associated with Prognosis of Prostate Cancer Patients - Lieb, Verena; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Bellut, Laura; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2022)
In the present study, we further analyzed the data obtained in our previous study, where we investigated the cell-free DNA (cfDNA) of 34 progressive prostate cancer patients via targeted sequencing. Here, we studied the occurrence and prognostic impact of sequence variants according to their clinical pathological significance (CPS) or their functional impact (FI) in 23 DNA damage repair (DDR) genes with a focus on the ATM serine/threonine kinase gene (ATM). All patients had at least one DDR gene with a CPS or FI variant. Kaplan-Meier analysis indicated that the group with a higher number of CPS variants in DDR genes had a shorter time to treatment change (TTC) compared to the group with a lower number of CPS variants (p = 0.038). Analysis of each DDR gene revealed that CPS variants in the ATM gene and FI variants in the nibrin (NBN) gene showed a shorter TTC (p = 0.034 and p = 0.042). In addition, patients with CPS variants in the ATM gene had shorter overall survival (OS; p = 0.022) and disease-specific survival (DSS; p = 0.010) than patients without these variants. Interestingly, patients with CPS variants in seven DDR genes possessed a better OS (p = 0.008) and DSS (p = 0.009), and patients with FI variants in four DDR genes showed a better OS (p = 0.007) and DSS (p = 0.008). Together, these findings demonstrated that the analysis of cfDNA for gene variants in DDR genes provides prognostic information that may be helpful for future temporal and targeted treatment decisions for advanced PCa patients.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ATM; cfDNA; DDR genes; NBN; prognosis; prostate cancer; sequence variants

Cell-free dna variant sequencing using plasma and ar-v7 testing of circulating tumor cells in prostate cancer patients - Lieb, Verena; Bellut, Laura; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2021)
Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted sequencing, for sequence variants and for the occurrence of CTCs, with a focus on androgen receptor splice variant 7 (AR-V7)-positive CTCs. The cfDNA content was associated with overall survival (OS; p = 0.014), disease-specific survival (DSS; p = 0.004), and time to treatment change (TTC; p = 0.001). Moreover, when considering all sequence variants grouped by their functional impact and allele frequency, a significant association with TTC (p = 0.017) was observed. When investigating only pathogenic or likely pathogenic gene variants, variants of the BRCA1 gene (p = 0.029) and the AR ligand-binding domain (p = 0.050) were associated with a shorter TTC. Likewise, the presence of CTCs was associated with a shorter TTC (p = 0.031). The presence of AR-V7-positive CTCs was associated with TTC (p < 0.001) in Kaplan–Meier analysis. Interestingly, all patients with AR-V7-positive CTCs also carried TP53 point mutations. Altogether, analysis of cfDNA and CTCs can provide complementary information that may support temporal and targeted treatment decisions and may elucidate the optimal choice within the variety of therapy options for advanced PCa patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: CfDNA; CTCs; Prognosis; prostate cancer; Sequence variants

Combined miR-486 and GP88 (Progranulin) Serum Levels Are Suggested as Supportive Biomarkers for Therapy Decision in Elderly Prostate Cancer Patients - Fichte, Alexander; Neumann, Anna-Dorothea; Weigelt, Katrin; Guzman, Juan; Jansen, Thilo; Keinert, Julia; Serrero, Ginette; Yue, Binbin; Stöhr, Robert; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2022)
Our study aimed to assess the applicability of miR-486 in combination with soluble GP88 protein as a diagnostic and/or predictive biomarker for prostate cancer (PCa) patients. miR-486 and GP88 levels in serum samples from 136 patients undergoing MRI-guided biopsy of the prostate were assessed by qRT–PCR and ELISA, respectively. Of these, 86 patients received a histologically confirmed diagnosis of PCa. Neither marker showed an association with the diagnosis of cancer. PCa patients were separated based on (i) treatment into patients with active surveillance or patients with any type of curative treatment and (ii) age into elderly (>68 years) patients and younger patients (≤68 years). In elderly patients (N = 41) with the intention of curative treatment at optimized cut-off values, significantly higher GP88 levels (p = 0.018) and lower miR-486 levels (p = 0.014) were observed. The total PSA level and ISUP biopsy grade were used in a baseline model for predicting definitive therapy. The baseline model exhibited an area under the curve (AUC) of 0.783 (p = 0.005). The addition of the serum biomarkers miR-486 and GP88 to the baseline model yielded an improved model with an AUC of 0.808 (p = 0.002). Altogether, combined miR-486 and GP88 serum levels are associated with and are therefore suggested as supportive biomarkers for therapy decisions, particularly in elderly PCa patients.
CRIS-Team Scopus Importer:2022-06-03
Keywords: age; miRNAs; predictive biomarker; progranulin; prostate cancer; serum level

Expression of AR-V7 (Androgen receptor variant 7) protein in granular cytoplasmic structures is an independent prognostic factor in prostate cancer patients - König, Paul; Eckstein, Markus; Jung, Rudolf; Abdulrahman, Amer; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Hayashi, Jun; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (Cancers, 2020)
Prostate cancer (PCa) is the second most common cancer, causing morbidity and mortality among men world-wide. The expression of the androgen receptor (AR) and its splice variants is a crucial factor of prostate cancer biology that has not been comprehensively studied in PCa tumors. The aim of this study was to characterize the protein expression of the AR and its splice variant, AR-V7, and their subcellular distributions in PCa by immunohistochemistry and to correlate the results to the clinicopathological data and prognosis. Immunohistochemical staining for AR and AR-V7 was performed on a tissue microarray (TMA) with specimens from 410 PCa patients using an immunoreactive score (IRS) or only the percentage of AR-V7 staining in cytoplasmic granules. Nuclear or cytoplasmic AR staining was not associated with prognosis. AR-V7 staining was only occasionally observed in the nucleus. However, AR-V7 staining in the cytoplasm or in cytoplasmic granules was associated with relapse-free survival (RFS). AR-V7 staining of the cytoplasm was associated with a shorter RFS, whereas AR-V7 staining of cytoplasmic granules was associated with a longer RFS. In a multivariate Cox’s regression analysis, only negative (<5%) AR-V7 staining of cytoplasmic granules remained an independent prognostic factor for RFS (HR = 5.3; p = 0.006). In a further subgroup analysis by multivariate Cox’s regression analysis, AR-V7 was an independent prognostic factor in the following groups: age ≤ 65 (HR = 9.7; p = 0.029), negative CK20 staining (HR = 7.0; p = 0.008), and positive perineural invasion (HR = 3.7; p = 0.034). Altogether, AR-V7 protein in granular cytoplasmic structures is an independent prognostic factor for RFS in PCa patients.
CRIS-Team Scopus Importer:2020-09-25
Keywords: AR; AR-V7; Gleason score; Perineural invasion; Prognosis; Prostate cancer; Relapse-free survival; RFS

Expression of GP88 (Progranulin) Protein Is an Independent Prognostic Factor in Prostate Cancer Patients - Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; et al. (Cancers, 2019)
Prostate cancer, the second most common cancer, is still a major cause of morbidity and mortality among men worldwide. The expression of the survival and proliferation factor progranulin (GP88) has not yet been comprehensively studied in PCa tumors. The aim of this study was to characterize GP88 protein expression in PCa by immunohistochemistry and to correlate the findings to the clinico-pathological data and prognosis. Immunohistochemical staining for GP88 was performed by TMA with samples from 442 PCa patients using an immunoreactive score (IRS). Altogether, 233 cases (52.7%) with negative GP88 staining (IRS < 2) and 209 cases (47.3%) with positive GP88 staining (IRS >= 2) were analyzed. A significant positive correlation was found for the GP88 IRS with the PSA value at prostatectomy and the cytoplasmic cytokeratin 20 IRS, whereas it was negatively associated with follow-up times. The association of GP88 staining with prognosis was further studied by survival analyses (Kaplan-Meier, univariate and multivariate Cox's regression analysis). Increased GP88 protein expression appeared as an independent prognostic factor for overall, disease-specific and relapse-free survival in all PCa patients. Interestingly, in the subgroup of younger PCa patients (<= 65 years), GP88 positivity was associated with a 3.8-fold (p = 0.004), a 6.0-fold (p = 0.008) and a 3.7-fold (p = 0.003) increased risk for death, disease-specific death and occurrence of a relapse, respectively. In the PCa subgroup with negative CK20 staining, GP88 positivity was associated with a 1.8-fold (p = 0.018) and a 2.8-fold increased risk for death and disease-specific death (p = 0.028). Altogether, GP88 protein positivity appears to be an independent prognostic factor for PCa patients.
CRIS-Team WoS Importer:2020-01-28

MED12 and CDK8/19 Modulate Androgen Receptor Activity and Enzalutamide Response in Prostate Cancer - Andolfi, Chiara; Bartolini, Caterina; Morales, Elisa; Gündoğdu, Büşra; Puhr, Martin; Guzman, Juan; Wach, Sven; Taubert, Helge; Aigner, Achim; Eder, Iris E.; Handle, Florian; Culig, Zoran (Endocrinology, 2024)
Prostate cancer progression is driven by androgen receptor (AR) activity, which is a target for therapeutic approaches. Enzalutamide is an AR inhibitor that prolongs the survival of patients with advanced prostate cancer. However, resistance mechanisms arise and impair its efficacy. One of these mechanisms is the expression of AR-V7, a constitutively active AR splice variant. The Mediator complex is a multisubunit protein that modulates gene expression on a genome-wide scale. MED12 and cyclin-dependent kinase (CDK)8, or its paralog CDK19, are components of the kinase module that regulates the proliferation of prostate cancer cells. In this study, we investigated how MED12 and CDK8/19 influence cancer-driven processes in prostate cancer cell lines, focusing on AR activity and the enzalutamide response. We inhibited MED12 expression and CDK8/19 activity in LNCaP (AR+, enzalutamide-sensitive), 22Rv1 (AR-V7+, enzalutamide-resistant), and PC3 (AR−, enzalutamide-insensitive) cells. Both MED12 and CDK8/19 inhibition reduced cell proliferation in all cell lines, and MED12 inhibition reduced proliferation in the respective 3D spheroids. MED12 knockdown significantly inhibited c-Myc protein expression and signaling pathways. In 22Rv1 cells, it consistently inhibited the AR response, prostate-specific antigen (PSA) secretion, AR target genes, and AR-V7 expression. Combined with enzalutamide, MED12 inhibition additively decreased the AR activity in both LNCaP and 22Rv1 cells. CDK8/19 inhibition significantly decreased PSA secretion in LNCaP and 22Rv1 cells and, when combined with enzalutamide, additively reduced proliferation in 22Rv1 cells. Our study revealed that MED12 and CDK8/19 regulate AR activity and that their inhibition may modulate response to enzalutamide in prostate cancer.
CRIS-Team Scopus Importer:2024-09-27
Keywords: androgen receptor; enzalutamide; Mediator complex; prostate cancer

NanoLuc Binary Technology as a methodological approach: an important new tool for studying the localization of androgen receptor and androgen receptor splice variant V7 homo and heterodimers - Guzman, Juan; Weigelt, Katrin; Neumann, Anna-Dorothea; Tripal, Philipp; Schmid, Benjamin; Winter, Zoltan; Palmisano, Ralf; Culig, Zoran; Cronauer, Marcus V.; Muschler, Paul; Wullich, Bernd; Taubert, Helge; et al. (BMC Cancer, 2024)
Background: The androgen/androgen receptor (AR)-signaling axis plays a central role in prostate cancer (PCa). Upon androgen-binding the AR dimerizes with another AR, and translocates into the nucleus where the AR-dimer activates/inactivates androgen-dependent genes. Consequently, treatments for PCa are commonly based on androgen deprivation therapy (ADT). The clinical benefits of ADT are only transitory and most tumors develop mechanisms allowing the AR to bypass its need for physiological levels of circulating androgens. Clinical failure of ADT is often characterized by the synthesis of a constitutively active AR splice variant, termed AR-V7. AR-V7 mRNA expression is considered as a resistance mechanism following ADT. AR-V7 no longer needs androgenic stimuli for nuclear entry and/or dimerization. Methods: Our goal was to mechanistically decipher the interaction between full-length AR (AR-FL) and AR-V7 in AR-null HEK-293 cells using the NanoLuc Binary Technology under androgen stimulation and deprivation conditions. Results: Our data point toward a hypothesis that AR-FL/AR-FL homodimers form in the cytoplasm, whereas AR-V7/AR-V7 homodimers localize in the nucleus. However, after androgen stimulation, all the AR-FL/AR-FL, AR-FL/AR-V7 and AR-V7/AR-V7 dimers were localized in the nucleus. Conclusions: We showed that AR-FL and AR-V7 form heterodimers that localize to the nucleus, whereas AR-V7/AR-V7 dimers were found to localize in the absence of androgens in the nucleus.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Androgen receptor; Androgen receptor variant 7; Heterodimer; Homodimer; NanoLuc Binary Technology; Prostate cancer

Nanoparticle-complexed antimiRs for inhibiting tumor growth and metastasis in prostate carcinoma and melanoma - Kunz, Manfred; Brandl, Madeleine; Bhattacharya, Animesh; Nobereit-Siegel, Lars; Ewe, Alexander; Weirauch, Ulrike; Hering, Doreen; Reinert, Anja; Kalwa, Hermann; Guzman, Juan; Weigelt, Katrin; Wach, Sven; et al. (Journal of Nanobiotechnology, 2020)
Background: MiRNAs act as negative regulators of gene expression through target mRNA degradation or inhibition of its translation. In cancer, several miRNAs are upregulated and play crucial roles in tumorigenesis, making the inhibition of these oncomiRs an interesting therapeutic approach. This can be achieved by directly complementary single-stranded anti-miRNA oligonucleotides (antimiRs). A major bottleneck in antimiR therapy, however, is their efficient delivery. The nanoparticle formation with polyethylenimine (PEI) may be particularly promising, based on the PEI’s ability to electrostatically interact with oligonucleotides. This leads to their protection and supports delivery. In the present study, we explore for the first time PEI for antimiR formulation and delivery. We use the branched low molecular weight PEI F25-LMW for the complexation of different antimiRs, and analyse tumor- and metastasis-inhibitory effects of PEI/antimiR complexes in different tumor models. Results: In prostate carcinoma, transfection of antimiRs against miR-375 and miR-141 leads to tumor cell inhibition in 2D- and 3D-models. More importantly, an in vivo tumor therapy study in prostate carcinoma xenografts reveals anti-tumor effects of the PEI/antimiR complexes. In advanced melanoma and metastasis, we identify by a microRNA screen miR-150 as a particularly relevant oncomiR candidate, and validate this result in vitro and in vivo. Again, the systemic application of PEI/antimiR complexes inhibiting this miRNA, or the previously described antimiR-638, leads to profound tumor growth inhibition. These effects are associated with the upregulation of direct miRNA target genes. In a melanoma metastasis mouse model, anti-metastatic effects of PEI/antimiR treatment are observed as well. Conclusions: We thus describe PEI-based complexes as efficient platform for antimiR therapy, as determined in two different tumor entities using in vivo models of tumor growth or metastasis. Our study also highlights the therapeutic relevance of miR-375, miR-141, miR-150 and miR-638 as target miRNAs for antimiR-mediated inhibition.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-11-27
Keywords: Antimir; PEI; PEI/antimiR nanoparticles; Polyethylenimine; Therapeutic miRNA inhibition

Progranulin (GP88) is an independent prognostic factor for prostate cancer patients - Taubert, Helge; Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05